SISTEM PAKAR KONSULTASI DAN KONSELING MAHASISWA BERMASALAH DARI PRESPEKTIF KRISTIANI - Benget Rumahorbo; Darwis Robinson Manalu (Universitas Methodist Indonesia, 2016)
In general, students are more tightly when faced with personal problems, financial problems, family and moral issues. So often there is a failure as a result of the issue unresolved. So expect the need for an application or system for media consulting experts to find a solution in accordance with their respective problems. So that problems can be detected early, it can use an application that has been designed based on the data of experts that has been incorporated into the database of knowledge. These types of problems and solutions are dynamic based on user needs and new knowledge experts found. Categories are often problematic issues of personality, economics and finance, family, education and other social issues. Data experts will first be incorporated as early knowledge that has been given by the experts. Sources of data obtained from the experience of experts encountered during counseling in college. Then the inference engine will draw final conclusions based on searches that have been determined on the basis of the rules. The goal is student can perform expert counseling through applications designed. The method used in the search is a method Best First Search and search by the method of backward chaining. Results from this study is a useful application for counseling for troubled students